2015
DOI: 10.1038/npp.2015.126
|View full text |Cite
|
Sign up to set email alerts
|

Mice Lacking the Serotonin Htr2B Receptor Gene Present an Antipsychotic-Sensitive Schizophrenic-Like Phenotype

Abstract: Impulsivity and hyperactivity share common ground with numerous mental disorders, including schizophrenia. Recently, a populationspecific serotonin 2B (5-HT 2B ) receptor stop codon (ie, HTR2B Q20*) was reported to segregate with severely impulsive individuals, whereas 5-HT 2B mutant (Htr 2B − / − ) mice also showed high impulsivity. Interestingly, in the same cohort, early-onset schizophrenia was more prevalent in HTR2B Q*20 carriers. However, the putative role of 5-HT 2B receptor in the neurobiology of schiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
60
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 50 publications
3
60
1
Order By: Relevance
“…This result, together with the finding that 5-HT 2B R blockade inhibits haloperidol-induced DA outflow in the NAc but not in the striatum (Auclair et al, 2010), suggests that it may be possible to generate a clozapine-like neurochemical profile when combining 5-HT 2B R and DA-D 2 R antagonisms, as previously observed with other 5-HT receptors, such as the 5-HT 2A R (Ichikawa and Meltzer, 2000;Meltzer et al, 2003). Furthermore, that 5-HT 2B Rs could play a role in the neurobiology of schizophrenia has been recently suggested by a study performed in the constitutive 5-HT 2B R knock-out mice (Pitychoutis et al, 2015). At variance with the present findings, this study concluded that the genetic ablation of the 5-HT 2B R leads to a schizophrenic-like phenotype.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…This result, together with the finding that 5-HT 2B R blockade inhibits haloperidol-induced DA outflow in the NAc but not in the striatum (Auclair et al, 2010), suggests that it may be possible to generate a clozapine-like neurochemical profile when combining 5-HT 2B R and DA-D 2 R antagonisms, as previously observed with other 5-HT receptors, such as the 5-HT 2A R (Ichikawa and Meltzer, 2000;Meltzer et al, 2003). Furthermore, that 5-HT 2B Rs could play a role in the neurobiology of schizophrenia has been recently suggested by a study performed in the constitutive 5-HT 2B R knock-out mice (Pitychoutis et al, 2015). At variance with the present findings, this study concluded that the genetic ablation of the 5-HT 2B R leads to a schizophrenic-like phenotype.…”
Section: Discussionmentioning
confidence: 55%
“…In agreement with the role of 5-HT 2B Rs in brain maturation (Kolodziejczak et al, 2015), it is conceivable that the observed phenotype could result from profound neural adaptations triggered by the permanent lack of this receptor. However, the fact that acute pharmacological blockade of 5-HT 2B Rs phenocopied some behavioral responses observed in knock-out mice (Pitychoutis et al, 2015), points out that additional factors, such as the use of different species, may account for the different conclusion offered by the present study. Future investigations in animals chronically treated with 5-HT 2B R antagonists as well as in advanced genetic models, such as conditional 5-HT 2B R knock-out animals, are warranted to address this issue.…”
Section: Discussionmentioning
confidence: 62%
“…Indeed, Htr2b -/-mice were recently shown to display deficits in social interactions, as well as in learning and memory processes [54], and these processes require intact frontal lobe function. Along the same lines, the Q20* polymorphism, only found in the Finnish population, is associated with severe impulsivity [3], possibly caused by frontal lobe modulation.…”
Section: Discussionmentioning
confidence: 99%
“…Htr2b −/− mice are hyperactive and have deficits in pre-pulse inhibition of the startle response, social interaction, memory, and attention, and increases in wakefulness as well as impulsivity (Pitychoutis et al , 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Htr2b −/− mice are hyperactive and have deficits in pre-pulse inhibition of the startle response, social interaction, memory and attention, and increases in wakefulness as well as impulsivity. 37 HTR2B mutations are also associated with aggression in other species, such as pigs 38 and zebrafish. 39 In humans, a specific 5-HT2B receptor stop codon (HTR2B Q20*) observed in a Finnish male population segregates with severe impulsivity, psychosis and early-onset schizophrenia.…”
Section: Discussionmentioning
confidence: 99%